2007
DOI: 10.1515/jpem.2007.20.11.1199
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto's Thyroiditis in Children and Adolescents: A Retrospective Study on Clinical, Epidemiological and Laboratory Properties of the Disease

Abstract: Autoimmune thyroiditis is more frequent in females, and increases in frequency over age during childhood and adolescence. At the time of diagnosis, frequency of overt and subclinical hypothyroidism is similar to that of euthyroid goiter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
1
21

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 21 publications
9
55
1
21
Order By: Relevance
“…In a study from iodine-replete area, twenty-four patients (21%) were euthyroid, 48 (42%) had compensated hypothyroidism, and 42 (37%) had hypothyroidism (including two patients with transient hyperthyroidism reversed to hypothyroidism within weeks). There was no difference in clinical symptoms of hypothyroidism by thyroid status, except for a higher rate of constipation in the hypothyroid group (38). The fact that many children with lymphocytic thyroiditis do not have elevated levels of TSH indicates that the goiter may be caused by the lymphocytic infiltrations or by thyroid growth-stimulating immunoglobulins.…”
Section: Laboratory Findingsmentioning
confidence: 84%
See 1 more Smart Citation
“…In a study from iodine-replete area, twenty-four patients (21%) were euthyroid, 48 (42%) had compensated hypothyroidism, and 42 (37%) had hypothyroidism (including two patients with transient hyperthyroidism reversed to hypothyroidism within weeks). There was no difference in clinical symptoms of hypothyroidism by thyroid status, except for a higher rate of constipation in the hypothyroid group (38). The fact that many children with lymphocytic thyroiditis do not have elevated levels of TSH indicates that the goiter may be caused by the lymphocytic infiltrations or by thyroid growth-stimulating immunoglobulins.…”
Section: Laboratory Findingsmentioning
confidence: 84%
“…Upon admission, 18.6% of patients had complaints related to hypothyroidism (7.4% growth retardation, 4.9% weight gain and 6.3% other complaints related to hypothyroidism). Eighteen patients (11.1%) were diagnosed incidentally upon detection of goiter during routine examination (38). Staii et al reviewed 761 patients for which ultrasound guided thyroid fine needle aspiration biopsy were performed for nodule.…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…In this study we detected an association with family history somewhat higher than Demirbilek et al, who found that 40% of patients had a family history of thyroid disease. 12 The evolutionary study detected a trend towards an improved clinical course among patients diagnosed due to an accidental finding and a worse clinical course among those who showed clinical manifestations of thyroid disease. Fava et al 2 found a similar association.…”
Section: Discussionmentioning
confidence: 97%
“…Hemos detectado una asociación familiar algo superior a Demirbilek et al, que hallaron un 40% de pacientes con antecedentes familiares en su estudio. 12 En el estudio evolutivo, se detectó una tendencia a mejor evolución en los pacientes que habían sido diagnosticados por un hallazgo analítico casual y una peor en los que aparecieron con clínica tiroidea. Fava et al 2 encontraron una asociación semejante.…”
Section: Discussionunclassified